The Influence of Service Quality and Price on Shopeefood Generation Z Customer Satisfaction in Bandung City - Melati Rahma Anggraeni; Deni Solihin (Escalate : Economics and Business Journal, 2026)
The rapid growth of online food delivery services like ShopeeFood in Indonesia motivates this study, as service quality and price are crucial for Generation Z customer satisfaction in Bandung City despite complaints about drivers and shipping costs. This explanatory quantitative research targets a population of 659,583 Generation Z users (born 1997-2012), with a sample of 100 respondents selected via Slovin formula and purposive sampling (minimum 3 uses/month). A 5-point Likert questionnaire (valid r>0.1966, reliable α>0.70) was analyzed descriptively, with classical assumption tests, multiple linear regression, and t-F tests using SPSS 27. Results show significant partial effects of service quality (β=0.173, t=11.926, p=0.000) and price (β=0.172, t=8.604, p=0.000), and simultaneous effect (F=106.968, p=0.000, R=0.862), with high satisfaction at 91.83%. In conclusion, service quality and price positively and significantly influence Generation Z ShopeeFood satisfaction both partially and simultaneously; recommendations include enhancing service consistency for loyalty.